2013
DOI: 10.1177/0003319713501376
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Vascular Endothelial Growth Factor A and Inflammation in Patients With Peripheral Artery Disease

Abstract: We compared apoptosis, cellular oxidative stress, and inflammation of cultured endothelial cells treated with sera from 130 subjects with peripheral artery disease (PAD) and 36 control subjects with high burden of co-morbid conditions and cardiovascular risk factors. Secondly, we compared circulating inflammatory, antioxidant capacity, and vascular biomarkers between the groups. The groups were not significantly different (p>0.05) on apoptosis, hydrogen peroxide, hydroxyl radical antioxidant capacity, and nucl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
2
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(80 citation statements)
references
References 57 publications
3
74
2
1
Order By: Relevance
“…Epidemiological data relating circulating VEGF concentrations to CVD risk are inconclusive: Blann et al 17 observed elevated blood VEGF levels in patients with coronary or peripheral artery disease compared with healthy controls. Conversely, other investigators have reported decreased serum VEGF levels in patients with peripheral artery disease compared with control subjects 18 19. Taken together, the relation of circulating VEGF concentrations with atherosclerotic disease is unclear at present.…”
Section: Discussionmentioning
confidence: 87%
“…Epidemiological data relating circulating VEGF concentrations to CVD risk are inconclusive: Blann et al 17 observed elevated blood VEGF levels in patients with coronary or peripheral artery disease compared with healthy controls. Conversely, other investigators have reported decreased serum VEGF levels in patients with peripheral artery disease compared with control subjects 18 19. Taken together, the relation of circulating VEGF concentrations with atherosclerotic disease is unclear at present.…”
Section: Discussionmentioning
confidence: 87%
“…In brief, endothelial cells (purchased from Cell Applications, Inc., San Diego, CA, after passage 4; age of the donors is unknown) were initially cultured in MesoEndo Endothelial Cell Growth Medium (Cell Applications, Inc) followed by Endothelial Basal Medium supplemented with 10% fetal calf serum until the time of serum treatment, as described. 31, 32 Inter-individual variance is unlikely to contribute to observed differences because detector cells used for each in vitro study were from the same donor. For treatment, fetal calf serum was replaced with serum (10%; for 24–48 h) collected from our subjects.…”
Section: Methodsmentioning
confidence: 99%
“…For treatment, fetal calf serum was replaced with serum (10%; for 24–48 h) collected from our subjects. 31 Cells cultured in Endothelial Basal Medium supplemented with 10% fetal calf serum served as an additional control.…”
Section: Methodsmentioning
confidence: 99%
“…10 In PAD, exercise is associated with an increase in plasma levels of numerous inflammatory mediators, including thiobarbituric acid-reactive substances (formed as a byproduct of lipid peroxidation), thromboxane, interleukin-8, tumor necrosis factor-α, soluble intercellular adhesion molecule-1, vascular cell adhesion molecule-1, von Willebrand factor, E-selectin, and thrombomodulin. [87][88][89][90][91][92][93] Inflammatory mediators can aggravate endothelial dysfunction, and markers, such as interleukin-6, are inversely correlated with maximum treadmill performance. 94 When exercise impairment was evaluated by a series of walking tests, higher serum C-reactive protein and serum amyloid A concentrations were associated with reductions in 6-minute-walk distance, 4-meter walking velocity, and a summary performance score that combined performance in walking speed, standing balance, and time for 5 repeated chair rises.…”
Section: Inflammation and Oxidant Stressmentioning
confidence: 99%
“…107 For example, circulating concentrations of vascular endothelial growth factor are decreased in patients with PAD when compared with controls with other comorbid conditions. 93 Innovative anti-inflammatory therapies developed for other indications may have relevance for PAD. For example, intercellular adhesion molecules and vascular cell adhesion molecules play important roles in intracellular signaling and the immune and inflammatory responses and are elevated in patients with PAD.…”
Section: Inflammation and Oxidant Stressmentioning
confidence: 99%